Stratégie d’une junior minière française face au « risque social » : le cas du projet Fonts-Bouillants - Aurélien Reys; Sylvain Le Berre; Yann Gunzburger; Laurent Jammes (VertigO)
Social risk, i.e. the opposition of local populations, has now become one of the major issues for mineral exploration or exploitation projects. In France, protest movements against them have been holding back the mining revival desired by the government and the industry for over a decade. This article examines the trajectory of one of these projects which has been able to develop without facing any social mobilization or local resistance. Located in the French’s department of Nievre, it concerns gaseous deposits of helium and carbon dioxide and is being carried out by a French junior company recently created. The analysis is conducted through the prism of a grid that seeks to evaluate this risk for several mining projects within Canada. Our work offers the opportunity to revisit this grid by comparing the Canadian and French contexts, the latter being characterized by a decline since the 1990s. It also highlights the main reasons of the project’s success to date: its low direct impact on the environment and an effective communication strategy led by the company based on a storytelling marketing approach. At this stage, co-constructive dynamics are non-existent, mainly due to stakeholders' wish to not play a role other than that of secondary partner.